Identyfikacje pojęcia sprawiedliwości społecznej - Stoiński, Andrzej (Annales. Etyka w Życiu Gospodarczym, 2016)
In the 1840’s due to Luigi Taparelli and Antonio Rosmini emerged the term of “social justice”. From this time, its meaning has developed in many ways. The paper brings up some applications of the notion. In the literature of the subject one can find numerous identities of “social justice”. The article focuses on the identity of this term with justice framed as: legal, distributive, commutative, penal, and restorative. Some of these concepts assumes and requires existence of some kind of social persons. By briefly analysing those notions the author tries to show the specificity of particular types of meanings assigned to the social justice.